The Effect of Using Live Instagram and Q&A Strategy in Improving Students’ Speaking Skills at Senior High School 47 Jakarta - Sandy Maheswara; Mira Ermita; Dini Hidayati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to determine the effectiveness of using Instagram Live and the Q&A Strategy in improving students’ english speaking skills at Senior High School 47 Jakarta. The research employed a quasi-experimental design using a pretest–posttest control group design. The participants were 72 tenth-grade students divided into two groups: an experimental class that received treatment through Instagram Live sessions and a control class taught through the conventional Discussion and Q&A technique. The research instrument was an oral speaking test, measuring five indicators fluency, pronunciation, vocabulary, grammar, and comprehension administered both before and after treatment. The data were analyzed using an independent sample t-test, ANOVA, normality, and homogeneity tests. Results showed a significant difference between the experimental and control groups. The post-test mean score of the experimental class (79.11) was higher than the control class (70.72). The t-test indicated a significance value (Sig. 2-tailed) < 0.001 with t = 4.960 and a mean difference of 8.40 points. Thus, the null hypothesis (H₀) was rejected, proving that Instagram Live significantly improved students’ speaking skills. The findings conclude that Instagram Live effectively enhances students’ fluency, pronunciation, vocabulary mastery, and self-confidence. Moreover, this study highlights the potential of social media–based learning as an engaging and interactive strategy that fosters motivation, participation, and 21st-century communication competence.